Organizational Learning Processes and the Performance of the Malaysian Aviation Industry - Mohd Alwi, Noorhisham (2007)
The purpose of this study was to explore the link between organizational learning processes of knowledge acquisition, transfer and utilization and the performance of the Malaysian aviation industry. The study was guided by three research questions: 1) How was knowledge acquired in the manufacturing, maintenance, repair and overhaul of aircraft? 2) How was the acquired knowledge transferred and shared within the organizations? 3) In what ways were the knowledge utilized by the aeronautical engineers and technicians? A qualitative research design employing the case study method was used in conducting the study. Three case sites made up of two aircraft manufacturing organizations and one maintenance, repair and overhaul of aircraft facility were chosen. Eleven respondents were selected in the study using the snowballing technique. The selection of the respondents was based on the following criteria: i) they have aeronautical engineering background; ii) they were recipients of the knowledge and iii) they were involved in the transfer of the knowledge gained. Aeronautical engineers and technicians formed the core of the participating respondents. The primary data collection technique used in this case study was the interviews. Observations were made during visits to the case sites, and documents which include company profiles, training manuals and process charts were reviewed to supplement the data collection. The within case and cross-case analysis using the constant comparative method generated the categories. Triangulation, peer examination and member check were used to ascertain trustworthiness of the study. The findings suggested that knowledge has been acquired through four different processes: technology transfer; expert coaching; personal exploration and hands-on experience. The acquired knowledge was transferred and shared within the organizations through three different mechanics: in the form of documented operating procedures; mentoring; and in-house training activities. The respondents suggested that the knowledge gained was utilized to conform to customer requirements; for process integration and improvement; professional upgrading; and strengthening the organizational capability. Four conclusions were drawn from the study. First, the thoroughness of technological know-how acquisition processes among the Malaysian aeronautical engineers and technicians can be facilitated through the use of multiple experiential learning strategies. Second, in a complex high-tech learning system such as the Malaysian aviation industry, informal social interaction process of network mentoring and expert coaching at the workplace enhances tacit knowledge transfer. Third, knowledge transferred which is situated in nature, can lead to technological innovation and strengthen the Malaysian aviation organizational capability if the transfer process is complete. However, in a mature organization, if knowledge transfer is incomplete, the organization has a higher tendency of suffering from knowledge depletion through the departure of key personnels. Finally, organizational learning processes have contributed to the performance of the Malaysian aviation industry. The industry is being recognized as an aircraft service and structural parts provider by world class aircraft manufacturers.